2.79 μm Cr, Er:YSGG laser with a high energy realized by thermal bonding and concave end-face. (July 2023) - Chen, Yuwei; Sun, Dunlu; Zhang, Huili; Luo, Jianqiao; Quan, Cong; Han, Zhiyuan; Qiao, Yang; Wang, Zhentao; Cheng, Maojie
Highlights: Cr, Er:YSGG crystal with thermal bonding and concave end-face is pumped by Xenon lamp. Thermal distribution simulation shows thermal bonding can improve heat dissipation capability. Thermal focal length indicates concave end-face can compensate thermal lens effect. High single pulse energy of 3.48 J obtained for the concave thermal bonding Cr, Er:YSGG at 5 Hz. Maximum energy of 1.155 J and slope efficiency of 3.65 % are achieved for the concave thermal bonding Cr, Er:YSGG at 20 Hz. Abstract: We demonstrate the influence of thermal bonding and concave end-face on the 2.79 μm laser performance of Cr, Er:YSGG crystal. The simulation results of temperature distribution suggest that the two pure YSGG crystals bonded on the Cr, Er:YSGG as end-caps are beneficial to improve the heat dissipation capability. The experimental results of thermal focal length show that the thermal effects of un-bonding, planar thermal bonding, and concave thermal bonding Cr, Er:YSGG crystals are in descending tendency. The maximum output energies and slope efficiencies for concave thermal bonding Cr, Er:YSGG crystal are 3.480 J, 3.33 %@5 Hz; 2.126 J, 3.65 %@10 Hz; 1.384 J, 3.63 %@15 Hz; 1.155 J, 3.65 %@20 Hz, respectively, and the beam quality factors Mx 2 / My 2 are determined to be 7.68/8.63. The result is much better than the previous work, indicating that the xenon lamp pumped concave thermal bonding Cr, Er:YSGG crystal is a promising method to realize high energy laser output. All the results indicate that the thermal bonding and concave end-faces are promising methods to reduce the thermal effect and improve the laser performance of Cr, Er:YSGG crystal pumped by the xenon lamp.